PENGELOLAAN MUSEUM BAHARI SEBAGAI DAYA TARIK WISATA EDUKASI DI JAKARTA - Rizki Nurul Nugraha; Prili Diana Rosa (Sekolah Tinggi Pariwisata Mataram, 2022)
Tourism development in an area must be given more attention because tourism development will determine the future of tourism itself and for the welfare of the surrounding community. Telaga Arwana Cibubur is a tourist destination located on Jalan Jamboree RT.05/RW.06, Harjamukti, Cimanggis. Telaga Arwana Cibubur is a tourist attraction that presents a beautiful rural atmosphere in the middle of a metropolitan city, still requires special attention and the need for a strategy for tourism development. The purpose of this research is to analyze the strengths, weaknesses, opportunities and threats of the Telaga Arwana Cibubur tourist destination, then from the results of the analysis that has been done, a strategy will be formulated for the development of the Telaga Arwana Cibubur tourist destination. This research is a qualitative descriptive study, the data will be analyzed descriptively, then to determine the strategy for developing tourism destinations for Telaga Arwana Cibubur, it is carried out by using a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Data will be collected through literature study, observation and by conducting interviews. The final result of this research is a strategy for the development of Eretan Jumharto Beach tourist destinations in order to develop better and be able to compete with other tourist objects